2019
DOI: 10.2147/cmar.s199659
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA-218 regulates the chemo-sensitivity of cervical cancer cells through targeting survivin</p>

Abstract: Background: Cervical cancer is one of the most lethal malignancies among women in the world. Every year about 311,365 women die because of cervical cancer. Chemo-resistance is the main reason of the lethal malignancies, and the mechanism of chemo-resistance in cervical cancer still remains largely elusive. Purpose: Previous studies reported that microRNAs played important biological roles in the chemo-resistance in many types of cancers, in the present study we tried to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…[47][48][49] Additionally, targeting survivin enhanced tumour chemo-and radio-sensitivity. [50][51][52] Our data demonstrated that licochalcone A translationally regulates survivin expression, but exhibits no significant effect on mRNA level and protein stability. Importantly, licochalcone A-mediated survivin down-regulation is partly dependent on the suppression of EGFR downstream Akt and ERK1/2 signallings, which is consistent with the previous report that reduces survivin protein by brexpiprazole overcomes EGFR TKI resistance in lung and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…[47][48][49] Additionally, targeting survivin enhanced tumour chemo-and radio-sensitivity. [50][51][52] Our data demonstrated that licochalcone A translationally regulates survivin expression, but exhibits no significant effect on mRNA level and protein stability. Importantly, licochalcone A-mediated survivin down-regulation is partly dependent on the suppression of EGFR downstream Akt and ERK1/2 signallings, which is consistent with the previous report that reduces survivin protein by brexpiprazole overcomes EGFR TKI resistance in lung and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed suppression of transactivation of survivin through direct binding to its promoter, the small molecule inhibitors YM‐155 and terameprocol (EM‐1421) decreased survivin protein and induced apoptosis in human cancer cells 47‐49 . Additionally, targeting survivin enhanced tumour chemo‐ and radio‐sensitivity 50‐52 . Our data demonstrated that licochalcone A translationally regulates survivin expression, but exhibits no significant effect on mRNA level and protein stability.…”
Section: Discussionmentioning
confidence: 77%
“…A growing body of evidence suggested miR-218 as significantly downregulated in human cancer tissues compared to the adjacent non-cancerous tissues [ 54 , 55 ], including cervical cancer [ 56 ], where it plays a role as a tumor-suppressor miRNA. MiR-218 was found to be significantly downregulated in cisplatin-resistant HeLa and SiHa cells compared to parental controls reaching a 60% decrease in both cell lines [ 40 ] ( Table 1 ). Survivin, one of the well-known inhibitors of apoptosis, was identified as a miR-218 target, thus the suppression of this miR in HeLa and SiHa cells ensures cell survival through a survivin-dependent mechanism [ 40 ].…”
Section: Molecular Mechanisms Associated With Cisplatin Resistancementioning
confidence: 99%
“…Ectopic expression of miR-214 reduces the expression of the protective Bcl2-like 2 protein and increases the expression of the pro-apoptotic proteins Bax, caspase-9, caspase-8, and caspase-3 in CC cells, leading to enhanced apoptosis and CDDP sensitivity (Wang et al, 2013). Similarly, miRNA-218 can reduce the expression of survivin both in mRNA and protein level, a member of the inhibitor of apoptosis protein family, thereby increasing CDDP sensitivity in CC cells (Yu et al, 2019).…”
Section: Regulation Of Apoptosismentioning
confidence: 99%